The Use Of Authentic Materials In Improving Learners’ Understanding In Using Grammar: A Case Study At Pamulang University And Binus University - Anwar, Djasminar; Winiharti, Menik (Bina Nusantara University, 2012)
This study discusses the use of authentic materials for non-English Department Students at Pamulang University, Tangerang, and BINUS University, Jakarta. Both universities have classes of English III which uses published materials and TOEFL course books. Authentic materials are provided to support the materials in the compulsory textbook. It is done to encourage students to more understand the grammar. The approach used in this study involves a pre-test, quizzes, and a post test. All these tools are used to measure whether there is a progress of the students’ performance. The students’ progress is summarized and shown in tables. Additionally, at the end of the semester, after the post test is given, a questionnaire is distributed to the students to know the students’ opinion about the provided authentic materials.